Faktor Risiko dan Implementasi Program Pencegahan ISPA pada Balita di Wilayah Pesisir, Desa Wonokerto Kulon, Kecamatan Wonokerto, Kabupaten Pekalongan - Afrida Isnania Khoiro; Cahya Kamilatus Zahrah; Atut Indah Choisiyah; Jaya Maulana; Dewi Nugraheni Restu Mastuti (Jurnal Medika Nusantara, 2026)
Acute Respiratory Infection (ARI) remains a major public health problem among children under five years old, particularly in coastal areas characterized by relatively homogeneous environmental and behavioral conditions. Dense settlements, substandard housing environments, and a high prevalence of risk behaviors are assumed to increase ARI incidence; however, empirical evidence explaining how these risk factors operate within homogeneous coastal communities and how prevention programs influence epidemiological findings remains limited. This study aimed to analyze risk factors associated with ARI among under-five children in the coastal area of Wonokerto Kulon Village, Pekalongan Regency, and to explore the implementation of ARI prevention programs at the primary health care level. A case–control study design was employed using a mixed-methods sequential explanatory approach. The quantitative phase included 38 children under five, consisting of 19 ARI cases and 19 controls selected through consecutive sampling. Bivariate analysis was conducted using Fisher’s exact test to examine associations between individual child factors, physical housing environment, and family behavioral factors with ARI incidence. The qualitative phase involved in-depth interviews with key informants from the primary health center and was analyzed thematically to contextualize the quantitative findings. The results showed no statistically significant associations between individual child characteristics, physical housing conditions, or family behaviors and ARI incidence (p > 0.05). Qualitative findings indicated that risk factor exposure in the coastal community was widespread and relatively uniform, while ARI prevention programs were implemented but constrained by structural limitations and persistent risk behaviors. This study concludes that homogeneous exposure to risk factors limits their role as individual-level determinants of ARI, suggesting that prevention efforts in coastal areas should prioritize community-based interventions and collective environmental improvements rather than individual-focused approaches.